Prediction of future situation of land use/cover change and modeling sensitivity to pollution in Edku Lake, Egypt based on geospatial analyses - El-Hamid, Hazem T. Abd; El-Alfy, Muhammad A.; Elnaggar, Abdelhamid A. (GeoJournal, 2021)
Assessing land use/cover (LULC) change in coastal lakes is an essential process for sustainable development. Edku Lake is one of the most important lakes in the northern part of Nile Delta in Egypt. It is directly subject to severe anthropogenic activities. The main objectives of this work were to predict LULC changes within Edku Lake area and to develop a pollution sensitivity model using remote sensing data and modern geographical information system (GIS) techniques. Three Landsat images were acquired in 2000, 2011 and 2018. These images were preprocessed, geo-referenced and prepared for further supervised classification using the maximum likelihood classifier. Five LULC classes were found in the area (water, vegetation, urban, bare and fish farm). CA–Markov model was applied to predict LULC changes using IDRISI software between each two consequent years. A predicted LULC map was obtained for 2025. This map can provide suggestions for future urban and vegetative planning in the studied area. This area was subject to severe changes from 2000 to 2018. Fish farms were significantly increased during this period. The predicted LULC map for 2025 indicates that large vegetative areas will be converted into urban and fish farms. The pollution sensitivity model showed that the eastern parts of the lake are more sensitive to pollution compared with the rest of the lake. Accordingly, protection of biodiversity in Edku Lake can be achieved based on future scenarios and measuring sensitivity of environmental factors and surrounding activities.